Yield components and productivity of maize hybrids in function of NPK doses and drought stress in the critical phenological stages - Pias, Osmar Henrique de Castro; Lowe, Marcio André; Damian, Junior Melo; Santi, Antônio Luis; Trevisan, Renato (Revista de Ciências Agroveterinárias, 2018)
Water stress and nutritional deficiency are the main factors that affecting grain yield of maize crops. In this sense, the aim of this study was to evaluate the yield components and productivity of maize hybrids through the use of fertilizer levels and drought stress at different periods of the reproductive stage. The study was carried out in a greenhouse using plastic vases with 15 liter capacity. A randomized block design in a factorial scheme (3 x 4 x 3) with three repetitions was used. The factors were constituted by maize hybrids (P30F53, AS1551 and AG5011), fertilization levels (0, 0.5, 1 and 1.5 times the recommended dose) and drought stress (without deficit, deficit in tasseling (VT) and grain filling (R2). The plant height, stem diameter, number of spikes, spike length, dry matter and grain yield were evaluated. Regardless of hybrid, maize crop is more tolerant to water stress at the tasseling period when compared to grain filling stage. The AS1551 hybrid showed the most grain yield as well as being more tolerant to drought water and malnutrition. The non-application of NPK fertilizer restricted severely grain yield, and with increasing doses there was a significant increase in productivity. The proper soil fertilization in AS1551 and AG5011 hybrids mitigate the effects of drought stress when applied at grain filling stage.